PENGARUH KOMPETENSI KEPRIBADIAN GURU PPKn TERHADAP PERILAKU SISWA SMA NEGERI DI KOTA PEKANBARU - Oktavani, Gita Dwi; Erlinda, Sri; ', Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack : This research is motivated by problems that arise from interviews conducted by researchers that the violations are often done by students is like late, unplug in certain lessons, attribute offense, talking with friends, not making tasks, cheating, trespassing and eating at canteen during school hours , some even caught smoking in the school environment. This study aims to determine the influence of personality competence of civic education teachers on the behavior of high school students in Pekanbaru City. This research method is descriptive quantitative. The instrument used is a questionnaire consisting of 29 statements about teacher personality competence and 20 statements about student behavior. Data were analyzed by using simple linear regression. Thus the hypothesis which states "there is influence between the competence of personality of civic education teachers toward the behavior of high school students in Pekanbaru City" accepted this is proved by simple linear regression test. Counted Fcount of 34.818 and Ftable 3.89 obtained from the study of Ftable distribution list with N = 282, at a significant level of 5% thus can be known Fcount ≥ Ftable or 34.818 ≥ 3.89 then Ho is rejected, so the hypothesis is accepted. In the coefficient of determination test the value of R square 11.1% means, the contribution of Personality Competence of civic education teachers toward the behavior of high school students in Pekanbaru City is 11.1% while 88.9% is influenced by variables not included in this study. Based on the results of research can be concluded that the competence of personality of civic education teachers pertained very good with percentage equal to 93,13%, and for student behavior classified as very good with percentage equal to 90,87%. The better the personality competence of the civic education teachers the better the students' behavior.Keywords : Personality Competence, Student Behavior